(untitled) (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
This study aims to examine the influence of participative leadership style and organizational culture on job satisfaction through work-life balance as a mediator in the Semarang City Fire Department. This study uses a quantitative approach with 183 respondents from the Semarang City Fire Department. Data collection techniques were carried out through the distribution of instruments and observations to obtain a direct picture of the conditions and activities of employees. The data analysis technique used Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of the SmartPLS version 4 application. The results of the study indicate that participative leadership style has a significant and positive effect on work-life balance and job satisfaction. Organizational culture has a positive and significant effect on work-life balance and job satisfaction. In addition, work-life balance has been shown to have a positive and significant effect on job satisfaction, which indicates that work-life balance significantly mediates the relationship between participative leadership style and job satisfaction, as well as between organizational culture and job satisfaction. These findings indicate that leadership and organizational culture play an important role in work-life balance and job satisfaction.